Linking LMS usability with critical reading intention in teacher education: a CRIS assessment (TPB-Based) on PPG PGSD students - Otang Kurniaman; Bench G. Fabros; Eddy Noviana; Munjiatun Munjiatun; Guslinda Guslinda; Nugraheti Simulyasih SB; Yantoro Yantoro; Radini Radini; Beny Al Fajar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
The development of critical reading and critical thinking skills is essential in teacher education, particularly for pre-service elementary school teachers who are expected to evaluate information critically and guide students in higher-order literacy practices. The increasing use of Learning Management Systems (LMS) in higher education provides opportunities to support students’ engagement with academic texts. However, limited research has examined how LMS engagement relates to students’ intention to participate in critical reading activities within teacher education contexts. The present study examines the relationship between LMS engagement and pre-service (PPG) students’ intention to engage in critical reading, as measured by the Critical Reading Intention Scale (CRIS), based on the Theory of Planned Behavior (TPB). A quantitative survey design was employed involving 109 pre-service teacher students from three universities in Indonesia. Data were collected via an online questionnaire that measured LMS usability and critical reading intention. The data were analyzed using non-parametric statistical analysis. The results indicate a statistically significant relationship between LMS engagement and students’ critical reading intention (p < 0.05). These findings elucidate that LMS-supported learning environments may be associated with students’ attitudes, perceived norms, and perceived control regarding critical reading activities. The study highlights the potential role of LMS-based instructional design in supporting critical reading engagement in pre-service teacher education.